Short-term effects of Ahmed valve implantation on ocular biometry and corneal biomechanics in neovascular glaucoma - Ali Azimi; Alireza Attar; Aidin Meshksar; Hooman Razmi; Mohammad Hassan Jalalpour; Amirmohammad Fathian; Adele Yarmohammadi (BMC Research Notes)
Abstract Objective To evaluate the impact of Ahmed glaucoma valve (AGV) implantation on ocular biometric and corneal biomechanical parameters in patients with neovascular glaucoma (NVG), with the goal of understanding how these changes influence intraocular pressure (IOP) control, surgical outcomes, and long-term prognosis. Results Eighteen NVG patients (mean age: 57.44 ± 10.33 years) underwent AGV implantation. A significant reduction in IOP was observed, from 36.65 ± 12.3 mmHg preoperatively to 15.5 ± 2.64 mmHg postoperatively (p < 0.001). Axial length decreased from 23.42 ± 0.76 mm to 23.21 ± 0.76 mm (p < 0.001), while anterior chamber depth increased significantly (p = 0.037). Both corneal keratometry and central corneal thickness showed significant postoperative decreases (p < 0.001). Corneal biomechanical parameters such as peak distance and deformation amplitude increased significantly (p = 0.004 and p = 0.001, respectively), whereas no significant changes were noted in applanation lengths and velocities (p > 0.05). These findings suggest that AGV implantation leads to substantial alterations in ocular structure and biomechanics, which may contribute to improved clinical outcomes in NVG management.